2022
DOI: 10.3389/fneur.2022.905400
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral protection by remote ischemic post-conditioning in patients with ischemic stroke: A systematic review and meta-analysis of randomized controlled trials

Abstract: BackgroundThere is evidence that remote limb ischemic postconditioning (RIPostC) can reduce ischemia-reperfusion injury (IRI) and improve the prognosis of patients with ischemic stroke. However, so far, only few relevant clinical studies have been conducted. Therefore, we carried out a meta-analysis of eligible randomized controlled trials to compare the RIPostC group with a control group (no intervention or sham surgery) in patients with ischemic stroke.MethodsFour English-language publication databases, PubM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Conditioning is a widely applied therapeutic technique in which a potentially harmful stimuli is applied below the threshold for tissue damage, leading to the induction of endogenous neuroprotective pathways [ 148 ]. Remote ischemic post-conditioning is a conditioning mechanism widely studied in ischemic stroke and found to be safe and effective in both preclinical and clinical studies [ 149 , 150 ], and has demonstrated promising results in TBI [ 151 , 152 ]. While the mechanistic effects underlying ischemic post-conditioning are still being uncovered, it is known to increase expression of BDNF and promote neurogenesis and neuroplasticity, which may help to prevent neurodegeneration and maladaptive functional alterations following cerebral insults [ 148 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conditioning is a widely applied therapeutic technique in which a potentially harmful stimuli is applied below the threshold for tissue damage, leading to the induction of endogenous neuroprotective pathways [ 148 ]. Remote ischemic post-conditioning is a conditioning mechanism widely studied in ischemic stroke and found to be safe and effective in both preclinical and clinical studies [ 149 , 150 ], and has demonstrated promising results in TBI [ 151 , 152 ]. While the mechanistic effects underlying ischemic post-conditioning are still being uncovered, it is known to increase expression of BDNF and promote neurogenesis and neuroplasticity, which may help to prevent neurodegeneration and maladaptive functional alterations following cerebral insults [ 148 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conditioning is a widely applied therapeutic technique in which a potentially harmful stimuli is applied below the threshold for tissue damage, leading to the induction of endogenous neuroprotective pathways [115]. Remote ischemic post-conditioning is a conditioning mechanism widely studied in ischemic stroke and found to be safe and effective in both preclinical and clinical studies [116,117], and has demonstrated promising results in TBI [118,119]. While the mechanistic effects underlying ischemic post-conditioning are still being uncovered, it is known to increase expression of BDNF and promote neurogenesis and neuroplasticity, which may help to prevent neurodegeneration and maladaptive functional alterations following cerebral insults [115].…”
Section: Future Directions In Multimodal Tbi Treatmentmentioning
confidence: 99%
“…A recent systematic review concluded that it appeared to be safe, and there may be a suggestion of efficacy, but whether it is really effective remains to be determined. 10 It also highlighted how previous studies had been small and underpowered and that we now need larger definitive trials to confirm whether this treatment, which is been highly effective in animal models, translates into clinical benefit. The protocol for such a trial, SERIC-IVT, in which RIC is given as an adjunct to intravenous thrombolysis is also published in this issue.…”
mentioning
confidence: 99%